Pengaruh Pupuk Cair terhadap pH, Fe-larut, dan C-organik di Tanah Sulfat Masam Desa Danda Jaya - Mei Latifika Faridatus Arifa; Fakhrur Razie; Syaifuddin Syaifuddin (Acta Solum, 2024)
One of the challenges of acid sulfate soil is the high Fe content in the soil, thus effective processing is needed to address its toxicity. The purpose of this study was to determine the changes in soil pH, Fe solubility, and organic-C from liquid fertilizer in acid sulfate soil in Danda Jaya Village, as well as to determine the relationship between soluble Fe and soil pH, organic-C and soil pH, and soluble-Fe. This research was structured using a descriptive method by comparing the application of liquid fertilizer with a control. The study was conducted in the Chemistry, Physics, and Biology Laboratory of the Soil Department, Faculty of Agriculture, Lambung Mangkurat University. The results of the study showed that the application of liquid fertilizer was able to increase pH and organic-C and decrease Fe solubility. Additionally, there was a correlation between soluble-Fe and pH with a coefficient of -0,95, a correlation between organic-C and pH with a coefficient of 0,91, and a correlation between organic-C and soluble-Fe with a coefficient of -0.89. Furthermore, the equation for the relationships was soil pH = -0.002 soluble-Fe + 5.958, Soil pH = 0.30 organic-C + 4,43, and soluble Fe = -154.92 organic-C + 830.15.